2004
DOI: 10.1002/chir.20066
|View full text |Cite
|
Sign up to set email alerts
|

Memory effect of diethylamine mobile phase additive on chiral separations on polysaccharide stationary phases

Abstract: The existence of a memory effect for amine additives on polysaccharide chiral stationary phases has often been suggested, but not clearly demonstrated. Demonstration of this effect is made difficult by the uncertainty as to which analytes benefit from use of amine additives and, typically, an unclear history of column use. In this work, analytes were selected for differences in their behavior with and without additives. Columns were used with no prior history. A persistent memory effect was demonstrated on a C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 8 publications
0
14
0
1
Order By: Relevance
“…So-called memory effects with the use of amine modifiers with Chiralpak AD and similar stationary phases are well precedented. 12 In addition, as is often the case for enantioseparations carried out with very low modifier concentrations, small changes in modifier concentration were found to result in profound changes in chromatographic performance (Fig. 8A).…”
Section: Resultsmentioning
confidence: 93%
“…So-called memory effects with the use of amine modifiers with Chiralpak AD and similar stationary phases are well precedented. 12 In addition, as is often the case for enantioseparations carried out with very low modifier concentrations, small changes in modifier concentration were found to result in profound changes in chromatographic performance (Fig. 8A).…”
Section: Resultsmentioning
confidence: 93%
“…They are, for instance, used in polar organic solvent chromatography and normal-phase liquid chromatography: no aqueous buffers are applied in these mobile phases; thus, the ionization of the analytes is tuned by using organic acids and bases. Studies on mainly polysaccharide-derived CSPs have been made to investigate the effect of such acidic and basic additives on the chromatographic results [55,[68][69][70]. During these experiments a memory effect was noted: a phenomenon where these mobile-phase additives leave a trace on the chiral selector of the CSP.…”
Section: Additional Discussionmentioning
confidence: 99%
“…The consequences of this contamination are that the separation results are affected. Stringham et al [69] did some experiments on polysaccharide-based stationary phases where the memory effect of DEA was clearly shown.…”
Section: Additional Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Recently, we reported that both acidic and basic mobile phase additives have significant effects on the enantioseparation of amino acids and their derivatives using one of the polysaccharide based CSPs, Chiralpak AD, as the chiral stationary phase. [20][21][22][23][24][25][26] Alkyl sulfonic acids and primary amines have been demonstrated to be better additives compared to the recommended trifluoroacetic acid and triethylamine and diethylamine. Acidic additives, such as ethanesulfonic acid, have been proven to be beneficial for the enantionseparation not only for acidic analytes, but also for basic analytes.…”
mentioning
confidence: 98%